2000
DOI: 10.1046/j.1524-4725.2000.99235.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Rush Paraffin-Embedded Tangential Sections in the Management of Cutaneous Neoplasms

Abstract: The use of Mohs micrographic surgery in conjunction with rush formalin-fixed, paraffin-embedded tangential histologic sections provides the accuracy and tissue conservation of the Mohs procedure while ensuring more confident interpretation of histology in cases of lentigo maligna, lentigo maligna melanoma, dermatofibrosarcoma protuberans, atypical fibroxanthoma, and angiosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 52 publications
2
86
1
3
Order By: Relevance
“…With our technique, we take an initial margin of only 2 to 3 mm around the visible tumor. Our average number of stages to tumor clearance was 1.7, which is comparable to other reports of 1.9, 27 2.1, 21 and 2.3. 26 In contrast, our mean postoperative defect sizes tended to be smaller than those reported previously (2.5ϫ3.3 cm vs 4.2ϫ4.5 cm, respectively 26 ), while the mean initial lesion sizes were similar (1.5 ϫ 2.1 cm vs 1.7 ϫ 1.7 cm, respectively 26 ).…”
Section: Mohssupporting
confidence: 90%
See 2 more Smart Citations
“…With our technique, we take an initial margin of only 2 to 3 mm around the visible tumor. Our average number of stages to tumor clearance was 1.7, which is comparable to other reports of 1.9, 27 2.1, 21 and 2.3. 26 In contrast, our mean postoperative defect sizes tended to be smaller than those reported previously (2.5ϫ3.3 cm vs 4.2ϫ4.5 cm, respectively 26 ), while the mean initial lesion sizes were similar (1.5 ϫ 2.1 cm vs 1.7 ϫ 1.7 cm, respectively 26 ).…”
Section: Mohssupporting
confidence: 90%
“…3,[24][25][26][27] However, since most recurrences of LM do not occur until 3 to 5 years after initial excision, long-term follow-up is needed to determine the success rate of any treatment modality. Although many authors have reported on recurrence rates, 3,9,21,24,26,27 only a few have obtained longterm (5-year) follow-up. 9,24,26 Additionally, results may not be comparable because follow-up methods are not always adequately described.…”
Section: Mohsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified Mohs micrographic surgical procedure which utilised formalin-fixed, paraffin embedded tissue for an improved interpretation of histology of soft-tissue tumours was employed (Clayton et al, 2000). Micrographic layers of 2 -3 mm thick were excised to give an initial 1 cm lateral excision margin from the tumour or scar margin, except in one patient where the initial margin was 0.5 cm.…”
Section: Operative Methodsmentioning
confidence: 99%
“…In addition, MMS for melanoma has demonstrated a low recurrence rate of 0.5% for both in situ and invasive melanoma with a 5-year follow-up [56]. Some authors [52,[57][58][59][60] augment frozen section interpretation of LM with rushed permanent sections and immunoperoxidase staining of the tissue that has been removed.…”
Section: Mmsmentioning
confidence: 99%